Problems of Abuse of Rights in Civil Proceeding - Hovhannisyan, Vahe (Bulletin of Yerevan University C: Jurisprudence, 2025)
In the framework of this article, the author has comprehensively studied and analyzed the substantive elements and functional features of the institution of abuse of procedural rights in civil proceedings. The basis for the study was the need to identify the scope of bearers of the possibility of abuse of procedural rights and obligations, the content and manifestations of abuse, and the legal mechanisms for eliminating the consequences.It has been substantiated that the abuse of procedural rights is not identical to a classic offense, since in this case the subject of law acts in accordance with legal orders during its activities, uses its rights, or fulfills the formal obligations imposed on it by law, but violates or causes harm to the rights of other participants in the proceedings and to the public interests of the effective administration of justice. It has been substantiated that abuse of procedural rights is an independent form of unlawful conduct, which results in the participants in the proceedings exercising their procedural rights and obligations in bad faith, that is, with unlawful expectations or inconsistent with their intended purpose. Moreover, abuse of rights can also be committed by a person who is not the actual holder of the relevant procedural right, which is due to the distinction between the concepts of being the real and formal holder of a subjective right. The court may also determine the good faith of a participant in the proceedings in exercising procedural rights and fulfilling procedural obligations by assessing actions taken outside the framework of the proceedings in a given civil case.As a result of the analysis of the norms prohibiting abuse of rights, the author has concluded that in civil proceedings there is a presumption of good faith of the participants in the proceedings, which conditions the realization of the rights and obligations of the participants in the proceedings, as well as the existence of a positive obligation of the court to ensure their protection.The selection of judicial sanctions or other proportionate measures of legal influence applied to persons who have abused procedural rights or other opportunities has also been emphasized, which is the discretionary power of the court and is conditioned by the degree of effectiveness in eliminating and counteracting violations of the rights of the participants in the proceedings, as well as private and/or public interests in the administration of justice protected by law.
Keywords: abuse of rights; non-conscientious performance of duty; acting inconsistent with the intended purpose; real holder of the right; unlawful expectation; offense; unconscientious behavior; prohibition of abuse; presumption; means of legal influence; sanction; discretion